Carcass characteristics of the Malaysian serama chicken - Noraziah Muhammad Auni. (2012)
A study was conducted to investigate the differences of carcass characteristics between two sexes of Serama chickens. The characteristics that seen in the study is in term of live weight, carcass dressing percentage, carcass composition and lastly are the chemical composition of the breast meat between two sexes of Serama chickens. The breast muscle or known as pectoralis muscle samples were taken for the chemical composition determination. The breast parts (pectoralis muscle) are often used by the previous studies because this part have a little or no bone and will easy used for chemical analysis. From experiments carried out, it was found that the weight of live chickens and the carcass dressing percentage of chickens is not significantly different between males and females chickens. This condition may be due to the chickens has the same weight as being in the same age. Carcass composition derived from the experiments conducted also found no significant difference in weight of meats and bones. However, the fats contents between the male and female chickens are significantly different. Female serama chickens contain highest percentage of fat. Similarly, the results are same for the weight of giblets such liver, heart and gizzard. The composition of the chemical contents in serama chicken meat also showed no significant difference between male and female chickens. From the results obtained, the ash content between male and female is significantly different. However, the percentages of moisture, crude fat, crude protein content are not significantly different in both sexes. This shows both sexes of the chicken have the same nutritional value.